2019
DOI: 10.1039/c9sc01666j
|View full text |Cite
|
Sign up to set email alerts
|

Laser illumination-induced dramatic catalytic activity change on Au nanospheres

Abstract: In this work, the distinct catalytic properties of a single gold nanoparticle (GNP) after symmetry breaking were disclosed at the single-particle level for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…According to the experimental measurement, the number of pixels occupied by the rectangular light spot was 2161 at the central cross section and the calculated T was 16 mm. Therefore, according to Equation (12), it could be calculated that the divergence angle of the rectangular light spot was about 23 • , which is basically consistent with the average divergence angle calculated by the theoretical Equations (1)- (3).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…According to the experimental measurement, the number of pixels occupied by the rectangular light spot was 2161 at the central cross section and the calculated T was 16 mm. Therefore, according to Equation (12), it could be calculated that the divergence angle of the rectangular light spot was about 23 • , which is basically consistent with the average divergence angle calculated by the theoretical Equations (1)- (3).…”
Section: Methodssupporting
confidence: 82%
“…Lasers have been widely applied in many fields, such as medical treatment [1,2], laser illumination [3,4], laser detection [5,6] and satellite communication [7,8]. However, the intensity distribution of a laser is usually in a Gaussian profile, which is always required to be converted into a flat-top profile so as to achieve the desired effect, e.g., laser welding [9,10], an optical system of exposure machine [11], laser drilling [12,13] and laser projection [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…5-7 and demonstrated in Figure 3C and Table 1. [28][29][30] , plasmon-induced changes of nanocatalysts itself (morphology and active site rearrangement) [31][32] and hot carriers facilitated reactant-catalyst interaction. [33][34][35] We carried out several control experiments to measure the surface temperature of Au NRs during laser irradiation ( Figure S8) and its morphology after the plasmonic photocatalysis ( Figure S9), and found negligible temperature and morphology change, thus possible contributions from photothermal effect and morphology were ruled out.…”
Section: Identification Of the Activation Energy Of Rate-limiting Stementioning
confidence: 99%
“…Although the former causes softening of the NP without melting being confirmed, the role of the latter in deformation needs to be further identified. The photothermal effect on elongation of suspended gold NPs into NRs caused by 532-nm laser was also reported [2]. In addition, other research showed that optical stress can be used to bend a suspending gold nanorod (NR) in water by means of an LP laser beam of 1064 nm [6].…”
Section: Introductionmentioning
confidence: 84%
“…As shown in Figure 1a, the deformation and reshaping process of gold NP/NR is divided into six stages: Stage I: A spherical NP is heated to be softened by laser beam irradiation. The optical traction stretches the NP to be an elongated NR [1,2]. Stage II and III: An elongated NR with a pronounced necking (a dumbbell with a dent at the center).…”
Section: Introductionmentioning
confidence: 99%